Model Prediktor Prognosis Pasien Trauma Multipel Berdasarkan Lokasi Anatomis Cedera di RSSA Malang, Indonesia: Sub-Studi dalam Penyusunan Model Multikomponen: Hasil Penelitian - Prasetyadjati, Ari; Setijowati, Nanik; Irsan, Istan Irmansyah; Zaiyanah, Munsifah; Johan, Willy (PT Kalbe Farma Tbk., 2025)
Introduction: Management of trauma still poses a challenge in Indonesia without significant improvement in mortality rates in the last 12 years, especially in multiple trauma involving at least 2 organ systems. This study aims to predict the prognosis of multiple trauma patients treated at Saiful Anwar Hospital (RSSA) Malang based on the anatomical location of the injury. Methods: Retrospective cohort study of 506 multiple trauma patients in RSSA during 2021-2022. The analyses used a chi square test and logistic regression test to obtain a regression equation. Results: Multiple trauma cases in RSSA were dominated by males in productive age (15-54 years). Head injury was the most influential variable in predicting the prognosis of multiple trauma patients in hospital, followed by thoracic injury, spinal injury, and abdominal injury. The logistic regression model was quite capable of explaining the data (p=0.931; Hosmer-Lameshow test), while the area under the curve (AUC-ROC) for prognosis in hospital care from this equation was 0.706 with a 95% confidence interval of 0.653-0.759 (good category). Conclusion: Head injuries, thoracic injuries, abdominal injuries, and spinal injuries are predictors of mortality of trauma cases in hospital care in RSSA, Malang, Indonesia.